EFFECT OF LEAVES DEFOLIATION AND DATE OF DEFOLIATION ON YIELD OF SUNFLOWER PLANT(Helianthus annuus L.) IN GYPSYFEROUS SOIL - AL-Jobory, Kamil; Dirach, Firas (Iraqi Journal of Science, 2024)
The study was conducted at Field Crop Department Farms , College of Agriculture-University of Tikrit. The objective was to study the effect of several leaves defoliation : Non defoliation (control)D1, defoliation of lower 25% D2, upper 25% D3, lower 50% D4, upper 50% D5 of plant leaves ,defoliation of 25 D6, 40 D7 and 50% D8 of plant leaves along stem , and defoliation of all plant leaves D9. that took place at two stages of plant growth : Vegetative growth to head formation (R1) , and the period from heads opening to flowering on seed yield and its components of sunflower var. Euroflor. The experiment was designed according to RCBD with three replications. Agricultural practices were made according to recommendations. Results showed that defoliation of plant leaves reduced seed yield and its components , the highest reduction occurred when defoliation of all plant leaves by 30.7,46.6,42.3, 46.6, 70.8, 70.8,and 32.2% of head diameter, number of seed per head , kernel : husk ratio , weight of 1000 seed , seed yield , biological yield , and seed oil percentage, respectively. While increased percentage of non-fertilized seed by 47.7% compared with non defoliation. Defoliation of plant leaves during growth stage caused reduction in the number of seed per head and kernel : husk ratio by 5.2 and 3.6% , respectively. Defoliation of all plant leaves not different with non defoliation In harvest index . Significant interaction between defoliation (%) and stages of plant growth in all studied characters. In conclusion ,defoliation of 25% of plant leaves and above in gypsyferous soil caused reduction in seed yield and seed oil percentage. Most of nutrient materials storage and assimilated in stem transfer to the seeds , this case indicated by increase harvest index of the plants which removed all leaves .